2017
DOI: 10.1186/s12985-017-0710-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus in mainland China with an emphasis on genotype and subtype distribution

Abstract: Due to the low fidelity of the RNA-dependent RNA polymerase, Hepatitis C virus (HCV) mutates quite frequently. There are seven genetically divergent genotypes (GTs) distributed in the world, each of which contains several closely related subtypes. The peer-reviewed literatures reporting the prevalence rate of HCV GTs in Chinese hospitalized patients were identified by systematic searching of three electronic databases, and the prevalence rates were pooled through 137 qualified studies. The significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 61 publications
11
81
0
Order By: Relevance
“…Envelope sequence analysis showed that HCV 1b and 3b subtypes were the dominant epidemic genotypes in this crowd. Both genotypes were also the major HCV genotypes prevailing in southwestern China …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Envelope sequence analysis showed that HCV 1b and 3b subtypes were the dominant epidemic genotypes in this crowd. Both genotypes were also the major HCV genotypes prevailing in southwestern China …”
Section: Discussionsupporting
confidence: 91%
“…Both genotypes were also the major HCV genotypes prevailing in southwestern China. 6 It has been confirmed that the clustering HCV infection was caused by needle sharing in a rural clinic in the 1990s. This The HCV antibody positive rate in tested adult female sera was as high as 41.2%, of which 72.7% were also HCV RNA positive.…”
Section: Discussionmentioning
confidence: 97%
“…We have observed that the frequency of HCV subtypes in the southern and southwestern regions has undergone an important change in the last three decades, and the prevalence of genotypes 3 and 6 in these regions was much higher than in other regions after 2010, which could be a result of the unique geographical location, changing routes of HCV transmission and increasing population mobility. [28][29][30] Some southwestern provinces, especially Yunnan and Guangxi, are adjacent to the "Golden Triangle," an area overlapping the mountains of three countries (Myanmar, Laos, and Thailand) and regarded as one of Asia's two main opium-producing areas. These provinces have become critical transferring stations for drug trafficking from the "Golden Triangle" to China since the 1980s.…”
Section: Distribution Of Mixed Infection With Different Hcv Genotypesmentioning
confidence: 99%
“…2,3 Epidemiologic studies have indicated that HCV genotype 1 is the most common genotype in Chinese patients, although there is a wide diversity across the country. 4,5 The mainstay of treatment in China is pegylated interferon and ribavirin (PEG-IFN/RBV), but both sofosbuvir and the combinations of daclatasvir/asunaprevir, ombitasvir, paritaprevir/ritonavir/dasabuvir, and sofosbuvir/velpatasvir have also received approvals. [6][7][8][9][10][11][12] Another direct-acting antiviral agent (DAA) is the fixeddose combination of elbasvir (EBR) and grazoprevir (GZR), approved in the United States, Europe, and Canada for the treatment of HCV genotype 1 and 4 infection, in Japan for the treatment of HCV genotype 1 infection, and in Canada for use in combination with sofosbuvir for the treatment of HCV genotype 3 infection.…”
Section: Introductionmentioning
confidence: 99%